Effect Of Maleic Anhydride Grafting On Properties Of Bamboo And Jute Fibres Woven Fabric Reinforced Polylactic Acid Composites - Tham, Mun Wai (2022)
Polymers like polylactic acid (PLA) is environmentally friendly with good tensile properties. However, impact strength of PLA is low. Hence, mechanically stronger bamboo and jute fibre fabrics were used as reinforcement. In this study, bamboo fibre fabric/PLA and jute fibre fabric/PLA composites were fabricated and studied. Firstly, effect of fibre content; 20 and 30 wt% on the properties of composites.